Case Report and Literature Review of Spinal Glioblastoma Multiforme in Childhood - Pasaribu, Ulinta Purwati; Primasari, Mirna; Erawati, Dyah (Perhimpunan Dokter Spesialis Onkologi Radiasi Indonesia (PORI), 2023)
We report a case of a 15 year old girl, with weakness on the lower extremities and sensory loss especially on the right side. MRI showed an intramedullary intraspinal mass at thoracic to lumbar spine level (T10-L1). A partial resection was performed and the result of pathology anatomy was Glioblastoma multiforme (GBM) WHO grade IV. She received adjuvant chemotherapy and craniospinal irradiation.